ASSISTING STUDENTS TO ATTACK WRITING TASKS ON IELTS TEST WITH â€œPROBING TECHNIQUEâ€ - Tedi Rohadi (University of Kuningan, 2015)
Abstract: Â Writing section on IELTS test is commonly considered one of the most difficult parts of test.Â The test takers canâ€™t even understand what to do with the tasks provided. They eventually write without clearly knowing the expected direction. Therefore, there should be a fastest way to well equip students to successfully cope with such hindrances. This paper is an action research report of how to make students better understand and answer writing tasks on IELTS test by employing probing techniquesÂ as one of test taking strategies. The paper will preliminarily elaborate the characteristics or nature ofÂ IELTS test in general andÂ writing section consisting two different tasks in particular including its indicators of what expected kind of writing the testeesÂ should be aware of. It will then discuss probing techniques in details. The attack strategies and theirÂ sequential implementationÂ will afterward be discussed. The technique will assist students to respectively understand what and how to plan and write effectively on the test.Keywords: IELTS test, writing section, writing tasks, probing, attack strategies